High seebeck coefficient thermo-electrochemical cell using nickel hollow microspheres electrodes. (September 2020) - Burmistrov, Igor; Gorshkov, Nikolay; Kovyneva, Natalya; Kolesnikov, Evgeny; Khaidarov, Bekzod; Karunakaran, Gopalu; Cho, Eun-Bum; Kiselev, Nikolay; Artyukhov, Denis; Kuznetsov, Denis; Gorokhovsky, Alexander
Abstract: High-performance harvesting of waste heat energy and its conversion into electric energy via thermo-electrochemical cells is an essential strategy of renewable energy development. Even though there is a large amount of scientific research available, but due to expensive electrode materials and low efficiency, the thermo-electrochemical cells have not found practical application. Here we demonstrated thermo-electrochemical cell with nickel (Ni) hollow microspheres-based electrodes, provided the highest hypothetical Seebeck coefficient of 4.5 mV/K (for aqueous electrolyte based thermocells) until today and open-circuit voltage values of up to 0.2 V. High values of Seebeck coefficient provide the ability to collect low-temperature heat, and high output potential differences which allow to fabricate batteries for commercial power circuits for various microelectronic devices. This work also proposed a mechanism and science behind the electrode processes, which explains a extremely high values of the hypothetical Seebeck coefficient. This is the first time to use Ni hollow microsphere in thermo-electrochemical cell for heat harvesting and thermal energy conversion into electricity. Because of the low cost of Ni microspheres electrode-based developed thermo cells could be commercially feasible for harvesting low-quality thermal energy. Graphical abstract: Image 1 Highlights: Ni hollow microspheres as an effective electrode material for thermo-electrochemical cells are investigated. The Seebeck coefficient of thermocells with Ni hollow microspheres-based electrodes is the highest for aqueous electrolyte. The mechanism of the untypical behavior of the cell open-circuit potential temperature dependency is proposed. The proposed Ni-based electrodes for thermocells are scalable for practical implementation.